The Empowerment of Problem-Based Learning Models to Improve Students’ Quantitative Reasoning - Muhammad Muzaini; Muhammad Hasbi; Ernawati Ernawati; Kristiawati Kristiawati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2022)
Quantitative reasoning has been highlighted as essential for middle-school student learning, particularly for themes that require students to make sense of relationships between quantities, according to a growing body of evidence. As a result, the current study adds to the body of literature that explores the growth of students' quantitative reasoning through teaching models. This study uses measuring tools such as a quantitative reasoning test and an observation sheet. The randomized pre-test–post-test control group design has been used in this investigation. The study included 95 second-year middle school students from Pangkep, Makassar, South Sulawesi, who were split into two groups: experimental and control. The N-gain index, which has high, medium, and low categories, was used to calculate the improvement of students' quantitative reasoning exam results. The finding of the data, 86.0 % of students in the experimental class increased their quantitative reasoning exam scores in the high category, while only 46.6% of students in the control class improved their quantitative reasoning exam scores. Students' quantitative reasoning improves substantially more when they utilize the problem-based learning models to learn about the linear program than when they use direct learning. As a result, students' quantitative reasoning can be improved by using problem-based learning models.